(untitled) (International Conference on Education, Psychology and Humanities, 2026)
This article provides a comprehensive scientific and theoretical analysis of the role of language dialectics in ensuring cultural stability in society. It substantiates that language, as a socio-cultural phenomenon, serves as a key mechanism for maintaining the continuity of national values, traditions, and historical memory. The study also reveals the dialectical unity of language and culture, their interaction, and their significance in preserving cultural stability in the context of globalization.